Heparin-protamine Complexes and C-reactive Protein Induce Activation of the Classical Complement Pathway: Studies in Patients Undergoing Cardiac Surgery and In Vitro - Bruins, Peter; Velthuis, Henk te; Eerenberg-Belmer, Anke J. M.; Yazdanbakhsh, Aria P.; de Beaumont, Eddy M. F. H.; Eijsman, León; Trouwborst, Ad; Hack, Erik C. (Thrombosis and Haemostasis, 2000)
The administration of protamine to patients undergoing cardiopulmonary bypass (CPB) to neutralize heparin and to reduce the risk of bleeding, induces activation of the classical complement pathway mainly by heparin-protamine complexes. We investigated whether C-reactive protein (CRP) contributes to protamine-induced complement activation.In 24 patients during myocardial revascularization, we measured complement, CRP, and complement-CRP complexes, reflecting CRPmediated complement activation in vivo. We also incubated plasma from healthy volunteers and patients with heparin and protamine in vitro to study CRP-mediated complement activation. During CPB, CRP levels remained unchanged while C3 activation products increased. C4 activation occurred after protamine administration. CRP-complement complexes increased at the end of CPB and upon protamine administration. Incubation of plasma with heparin and protamine in vitro generated complement-CRP complexes, which was blocked by phosphorylcholine and stimulated by exogenous CRP. C4d-CRP complex formation after protamine administration correlated clinically with the incidence of postoperative arrhythmia.Protamine administration during cardiac surgery induces complement activation which in part is CRP-dependent, and correlates with postoperative arrhythmia.
Keywords: C-reactive protein; heparin; protamine; complement; extracorporeal circulation